Fluorescent macrocyclic chemosensor for Zn(II) detection at alkaline pH values. Issue 2 (1st February 2020) - Ambrosi, Gianluca; Micheloni, Mauro; Paderni, Daniele; Formica, Mauro; Giorgi, Luca; Fusi, Vieri
ABSTRACT: The new macrocyclic ligand L (28, 29-dimethoxy-27-oxa-8, 11, 14, 17, 25, 26-hexaazatetracyclo[22.2.1.1(2, 6).1(19, 23)]nonacosa-2, 4, 6(28), 19, 21, 23(29), 24, 26(1)-octaene) has been synthesised. It contains a tetramine chain and the 2, 5-bis(2-methoxy-3-metyl-phenyl)-1, 3, 4-oxadiazole (PPD-OMe) chromophore, acting as coordinating and sensing units, respectively. The fluorescent emission of L depends on the pH being highly fluorescent at pH = 2 and not emitting from pH >10. The studies highlighted that L is a PET mediated emitting chemosensor, being the PET effect regulated by the degree of the tetraamine protonation. L coordinates metal ions (Cu(II), Zn(II) and Cd(II)) in water giving rise to an OFF-ON fluorescent response for the presence of Zn(II) ion thus signalling its presence in the medium. This response is particularly notable at pH = 9 allowing to extend the Zn(II) sensing also in the alkaline pH field. Graphical abstract: